Strengthening of Adat Village and The Value of Local Wisdom in Bali in Prevention Commercial Sexual Exploitation of Children (CSEC) - I Made Wirya Darma; Ni Nyoman Juwita Arsawati; I Gusti Agung Ayu Mas Triwulandari (Fakultas Hukum, Universitas Warmadewa, 2021)
The negative impact of the development of the tourism industry, information technology and communication and transportation in addition to problems of poverty, unemployment, dropping out of school, and limited employment is still an unresolved problem, thus further encouraging the Commercial Sex Exploitation of Children. Through strengthening Desa Adat and regulating child protection in awig-awig or pararem regarding strengthening the position of children in Bali by incorporating the concept of local wisdom will certainly be able to reduce the number of sexual violence and child exploitation in Bali, so that synergy in solving positive legal cases will be easier effective, because if a case occurs, it will be resolved first within the scope of the village through prevailing customary law before continuing into the realm of positive law. Arranging and determining Awig-awig who adopt local wisdom concepts and values including Tri Hita Karana, Tri Kaya Parisudha, and Tat Twam Asi are able to reflect religious, ritual and upakara elements in preventing sexual violence and exploitation of children.